Nevus comedonicus on scalp: A rare site - Naveen N Kikkeri; Rashme Priyanka; H A Parshawanath (Wolters Kluwer Medknow Publications, 2015)
Nevus comedonicus is rare hamartoma of the pilosebaceous unit. Curiously the scalp is rarely involved. Here we are reporting 33-year-old male presenting with nevus comedonicus arranged linearly on the scalp. There was positive family history of similar lesion on the similar site. This case has been presented for its sheer rarity and atypical site.